Mandatory vs Flexible Retirement and the Functions of Counselling\ - McVeigh, Frank J. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper examines and analyzes retirement, mandatory and flexible, as a complex social pattern and process in Canada and the United States. The paper first focuses on social forces and trends — demographic, financial, physical, attitudinal and legal — leading society away from mandatory retirement and toward more flexible retirement. Second, it examines viable arguments for mandatory retirement and empirical verification of its limited impact on the labour force. It also analyzes complexities involved in the issue, particularly organized labour's ambivalence about mandatory retirement. Third, it suggests four important functions that counsellors can perform in preparing people for the realities of retirement. Policy implications for Canada with respect to retirement are indicated.